Association between CTL Precursor Frequency to HLA-C Mismatches and HLA-C Antigen Cell Surface Expression - Israeli, Moshe; Roelen, Dave L.; Carrington, Mary; Petersdorf, Effie Wang; Claas, Frans H. J.; Haasnoot, Geert W.; Oudshoorn, Machteld (Frontiers in Immunology, 2014)
Previous studies showed the relevance of the cytotoxic T cell precursor frequency assay (CTLp) for prediction of the outcome of HLA mismatched hematopoietic cell transplantation (HCT). Recently it has been shown that HLA-C cell surface expression is correlated with virus specific cytotoxic T cell responses and viremia control in HIV patients. The aim of the current study was to investigate the association between HLA-C antigen expression and the CTLp frequency to the mismatched HLA-C antigen. In total 115 recipient–donor pairs, for whom a successful CTLp assay was performed, were evaluated for this pilot study. All donor-recipient pairs were matched at 9/10 alleles with a single mismatch at the HLA-C locus. Antigen expression level of the mismatched HLA-C allele for each recipient and donor was based on the MFI values as described by Apps et al (Science, 2013). The cell surface expression of recipient’s mismatched HLA-C antigen was significantly lower among CTLp negative (n=59) compared to CTLp positive (n=56) pairs (154 and 193 MFI units, respectively; p=0.0031). This difference was more pronounced in donor-recipient pairs that were mismatched for amino-acid residue-116 located in the groove of the HLA-C antigen, suggesting the importance of peptide binding in the allo-recognition. Furthermore, in the particular case of low expression of the recipient mismatched HLA-C antigen (MFI<115), CTLp reactivity depended on HLA-C expression level in the donor; the median MFI of donor’s mismatched HLA-C antigen was 114 in CTLp negative cases (n=26), while in CTLp positive cases (n=15) the median MFI of donor’s HLA-C antigen was 193. (P=0.0093). We conclude that the expression level of the donor and recipient mismatched HLA-C antigens affect CTLp outcome. HLA-C antigen expression levels in combination with the CTLp assay may prove useful for the prediction of the clinical outcome of HLA-C mismatched HCT.